Experimental Investigation On Pedestrian Behaviour Walk In Inundation - Ghozali, Noraini (Universiti Sains Malaysia, 2018)
Walking velocity of pedestrians is governed by many influencing factors such as Body Mass Index of Pedestrian, behaviour of pedestrian and type of obstacle facing. Several approaches for determining the pedestrian walking velocity have been done by experiment in laboratory. Federal Highway Administration (FHWA) Manual on Uniform Traffic Control Devices for Streets and Highways includes a walking velocity of 1.2 m/s with zero elderly pedestrian involved. Many research have study about how to evacuate from danger area to safe area by considering the maximum height of water and only on walking velocity at traffic signal not in water. However, so far not much study on the velocity of human while in water. Besides, this study relatively rare because there much lacking in evacuation process especially in Malaysia. Therefore, this study have two main objective is to determine empirical data of walking velocity of human during inundation for different Body Mass Index (BMI) and to simulate evacuation process during flood disaster. In this study, implementation of experiments under laboratory conditions with 8 pedestrian and extraction of trajectories by video analysis walking in water and without water. The data analysed for each task given with one directional flow of pedestrian with different level of water 0.08m, 0.43m and 0.9m. The result show that average walking velocity for female is lower than female and pedestrian who has normal Body Mass Index (BMI) will move faster in shallow water. Within three different level of water show that high Body Mass Index have been move faster in deep water because of balancing of buoyancy force. Therefore, the velocity of walking pedestrian slower when walkingdeeper in water. The differences is about 50 % from the normal walking velocity in straight line when walking in water in depth 0.9m. The results are of particular importance for the future evacuation process when flood occurs or emergency response plan.